Polymers in the Blender. Issue 18 (18th August 2020) - Junkers, Tanja
Abstract: Ever since the birth of controlled polymerizations, polymer synthesis always strived toward distributions that are as narrowly dispersed as possible. Yet, such polymers are not always advantageous, and only recently methods have started to develop that allow to create polymers with controllable molecular weight and dispersity. Stretching beyond that, there are also now tools to create distributions of any shape. This level of control, even if this is just the start of these endeavors, has tremendous potential for developing materials with superior and more precise physical properties. The principles for the synthesis of different molecular weight distributions shapes are introduced and discussed. Abstract : Since the birth of controlled polymerizations, scientists always strived toward polymers with low dispersity. Yet, such polymers are not always advantageous, and only recently methods have started to develop that allow to create polymers with controllable molecular weight distribution shape. These novel methods have tremendous potential for developing materials with superior and more precise physical properties.